May Measurement Month 2019: an analysis of blood pressure screening results from Taiwan. (20th May 2021) - Lin, Hung-Ju; Pan, Heng-Yu; Beaney, Thomas; Partington, Giles; Poulter, Neil R; Chen, Wen-Jone; Wang, Tzung-Dau
Abstract: To bolster the awareness of high blood pressure (BP) and to monitor the trend of hypertension control rate. Similar to May Measurement Month (MMM) 2017 and 2018 campaigns, we conducted the MMM 2019 campaign in 643 community pharmacies across Taiwan, and recruited adults aged 20 years or over in May and June of 2019. After filling in an anonymous questionnaire regarding medical history and lifestyle habits and having 10-min sitting rest, pharmacists took triplicate upper-arm BP readings on participants using an automated oscillometric sphygmomanometer. The means of the second and third BP readings were used as the screening BP estimates. Hypertension was defined if one of the followings was met: use of antihypertensive medications, systolic BP ≥140 mmHg, or diastolic BP ≥90 mmHg. Controlled BP was defined as BP of <140/90 mmHg. Of the 24 851 participants enrolled (mean age, 55.8 ± 15.2 years), 12 427 (50.0%) were women. Among 12 351 (49.7%) participants with hypertension, 10 463 (84.7%) were aware of their high BP, and 10 142 (82.1%) received antihypertensive medications. While 59.2% of all hypertensive participants had controlled BP, the BP control rate was 72.0% in treated hypertensive participants. MMM campaigns offer a feasible way to monitor the trends in both awareness and control of hypertension. This nationwide annual BP screening campaign, from 2017 to 2019, demonstrated continued improvement in hypertension control in Taiwan.